THE IMPLEMENTATION OF TEACHING PERSONAL SOCIAL RESPONSIBILITY (TPSR) MODELS TO IMPROVE STUDENT RESPONSIBILITY ATTITUDE AT STKIP PASUNDAN CIMAHI - Supriadi, Dedi (Program Pascasarjana Universitas Negeri Jakarta, 2016)
The purpose of this study is to see the improvement of PJKR studentsâ responsibility by applying TPSR learning model in volleyball learning. The method used to uncover these issues was experimental method with randomized pretest-posttest control group design. The samples were all students of class VII E and J which were taken by means of cluster random sampling. They are students of the fifth semester in STKIP Pasundan Cimahi. The study was conducted in 8 weeks. The instrument used was a responsibility questionnaire that has had its validity and reliability measured. The data obtained were analyzed using SPSS 17 through Paired Samples t-test. The results revealed that Â TPSR learning model increases PJKR studentsâ responsibility attitude in STKIP Pasundan Cimahi. Furthermore, there is no effect of the conventional learning model to increase PJKR studentsâ responsibility attitude in STKIP Pasundan Cimahi. Based on these results, it can be concluded that the TPSR learning model significantly influences the attitude of responsibility for PJKR studentsâ improvement in STKIP Pasundan Cimahi compared to conventional learning models.